Fenomena Joki Pantarlih pada Persiapan Pemilu 2024 di KecamatanWonokromo Kota Surabaya - Herlambang, Muhammad Reza; Fauzi, Agus Machfud (Paradigma, 2024)
There were still many frauds allegedly committed by Pantarlih ahead of the 2024 ELECTION. Violations occurred in 374 TPS (Polling Places from 2,878 TPS. There were 378 violations. Pantarlih did not stick stickers in 63 TPS. Pantarlih did not register new voters in 11 TPS. Pantarlih did not record disability information. 55 polling stations, not yet checked, stickers were pasted on 8 polling stations. Other violations 194 polling stations. The research uses the title Jockey Pantarlih Phenomenon in Preparations for the 2024 Election in Wonokromo District, Surabaya City. The research took place in the election location taking into account the researcher, namely Wonokromo District, Surabaya City, East Java. Subjects research by political election officials in Wonokromo sub-district and also jockeys who have a big role in matching data and also updating data on permanent voters in the implementation of the election, using Alferd Schutz's phenomenological theory, namely about Motive, Goal (In Order to Motive), the jockey's background is oriented politics is used to secure votes in the General Election, so in essence it is the objective motive, the aim of the person carrying out political jockeying is oriented towards accommodating political interests used to secure and condition the votes in the General Election by certain groups or certain individuals. Pantarlih jockeys in preparation for the 2024 elections in Wonokromo District, Surabaya City, according to data found in the field, there are individuals who are pantarlih jockeys who are assisted by regional officials, namely the RT head and RW head. The background to the phenomenon of pentarlih jockeys in the 2024 elections in the Wonokromo sub-district, Surabaya City, according to data found in the field, is that there are many political orientations by individuals who are contesting in the elections, such as legislative candidates, certain groups and parties. Keywords: Election, Jockey Pantarlih Phenomenon, Surabaya